2013
DOI: 10.1021/ja4058794
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and Kinetic Destabilization of Magnesium Hydride Using Mg–In Solid Solution Alloys

Abstract: Efforts to thermodynamically destabilize magnesium hydride (MgH2), so that it can be used for practical hydrogen storage applications, have been a difficult challenge that has eluded scientists for decades. This letter reports that MgH2 can indeed be destabilized by forming solid solution alloys of magnesium with group III and IVB elements, such as indium. Results of this research showed that the equilibrium hydrogen pressure of a Mg-0.1In alloy is 70% higher than that of pure MgH2. The temperature at 1 bar hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(61 citation statements)
references
References 19 publications
2
59
0
Order By: Relevance
“…These results strongly suggest that Mg and/or Mg 3 Ag formed a solid solution with In. [16][17][18]23 the In atoms dissolved in MgAg to form (Mg, In)Ag, as conrmed by XRD renement. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results strongly suggest that Mg and/or Mg 3 Ag formed a solid solution with In. [16][17][18]23 the In atoms dissolved in MgAg to form (Mg, In)Ag, as conrmed by XRD renement. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 However, its practical application as a hydrogen storage material has been plagued by sluggish hydrogen absorption/desorption kinetics and high thermostability. 6 To address the aforementioned problems, a simple but effective strategy, i.e., alloying Mg with other elements to form Mg-based compounds [7][8][9][10][11][12][13] or solid solutions, [14][15][16][17] was proposed. 4 and 5) and (ii) the strong Mg-H ionic bond.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research efforts, including optimization of the hydride materials, have been reported elsewhere [12,16,19]. Initially, in order to verify thermodynamic compatibility of the two hydride candidate materials, hydrogen equilibrium pressures of MgH 2 and TiMnV were characterized using a Sievert-type apparatus (PCT-Pro 2000).…”
Section: Hydride Materialsmentioning
confidence: 99%
“…However, pure MgH 2 , is known to have poor kinetic rates for both the dehydrogenation and hydrogenation reactions. Fortunately, recent progresses on hydrogen storage materials have shown that several nano-catalyzed Mg materials [12][13][14][15][16][17] are capable of absorbing a significant amount of hydrogen at room temperature. These findings have paved the way to practical application of Mg-based hydrides.…”
Section: Introductionmentioning
confidence: 99%
“…The ensuing large decomposition enthalpy of 75 kJ mol -1 H 2 results in relatively high desorption temperatures (>300 °C) coupled with a slow hydrogen diffusion rate, limiting its practical applications. 5 Different approaches such as catalysis, 6,7 alloying, 8,9 composite formation 10,11 and nanostructuring [12][13][14] have been employed to improve the hydrogen uptake/release kinetics and thermodynamics of MgH 2 . One of the most widely used strategies is to reduce the MgH 2 particle size by mechanical ball milling, hence lowering the activation energy of desorption.…”
Section: Introductionmentioning
confidence: 99%